Návrh a výroba vakuové formy pro sériové tváření plastů - Tišnovský, Jakub (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2019)
Tato diplomová práce se zabývá návrhem a výrobou formy pro sériovou výrobu plastových dílů vakuovým tvářením. Práce je rozdělena do 2 hlavních kapitol. Teoretická část obsahuje rozbor technologie třískového obrábění. V experimentální části práce je řešena konstrukce formy v softwaru PowerShape a následuje podrobný rozbor výroby modelu pro zaformování a samotné formy. Závěrem experimentální části je pojednáno o ručním dokončení formy a kontrole formy. Práce je ukončena technicko-ekonomickým zhodnocením, ve kterém jsou řešeny náklady na výrobu formy.

This diploma thesis deals with the proposal and production of a mold for series production of plastic parts by vacuum forming. The thesis is divided into 2 main chapters. The theoretical part includes analysis of chip machining technology. The experimental part focuses on solving the design of the mold in PowerShape software, a detailed analysis of making of the model for casting and about making of the mold themselves. In the last part the manual completion and verification of the mold is discussed. Thesis is terminated by technical-economic evaluation, in which is discussed about production costs.
A proposal and production of vacuum mold for serial production of plastic forming
Keywords: Forma; vakuové tváření; frézování; PowerShape; PowerMill; Mold; vacuum forming; milling; PowerShape; PowerMill